Book Review: Islamic Law in Circulation: Shāfiʿī Texts Across the Indian Ocean and the Mediterranean, by Mahmood Kooria, Cambridge University Press, 2021. 240 pp. ISBN: 9781108481461 - Muhammad Fauzinudin Faiz; Syuhood B. Kooria (Indonesian Journal of Islamic Law, 2025)
This article reviews Islamic Law in Circulation: Shāfiʿī Texts Across the Indian Ocean and the Mediterranean by Mahmood Kooria, which explores the transmission of Islamic legal texts within maritime networks across the Indian Ocean and the Mediterranean. Kooria introduces the concept of "maritime intellectuals" to explain scholar-merchants' dual role in disseminating Islamic legal knowledge. Employing an interdisciplinary approach that integrates philological studies, maritime history, and social network analysis, the book offers new insights into the dynamics of Islamic legal circulation. While the book excels in manuscript analysis and the use of multilingual sources, its limitations lie in the lack of engagement with oral traditions and the under-representation of women's roles in Islamic scholarly networks. Overall, this work significantly contributes to studying Islamic legal history and the global circulation of knowledge.